Pengembangan Pengembangan Microlearning pada Materi Getaran, Gelombang dan Bunyi dalam Kehidupan Sehari-Hari untuk Peserta Didik Kelas VIII Sekolah Menengah Pertama - Teguh Budi Setiada; Achmad Noor Fatirul; Djoko Adi Waluyo (SPEJ (Science and Physic Education Journal), 2022)
Abstract: This research aims to produce a product in the form of Microlearning that students of class VIII SMP can use on vibration, wave, and sound material in everyday life. Research conducted in developing Microlearning on the pulse, ripple, and suitable material for class VIII SMP students, which has been carried out in sequential steps in obtaining product feasibility, was carried out by design experts of 83%, material experts of 82.3%, and media experts of 82.8% which means the product is suitable for use and can be followed up in trials on students in learning. The instrument used for product trials in the field obtained validity test results using a product-moment correlation of 0.266 (the correlation coefficient value was more significant than the Product Moment r-table matter). It said that the instrument in this study was valid or could measure the variables studied. The results of the reliability test were 0.920 (this value was more significant than the r-table value of 0.6), meaning that the results of the respondents' answers were reliable. In other words that if the same research were carried out at different times, the respondents would give the same answer. In conclusion, learning media products for developing microlearning video content on vibrations, waves, and sound materials for students of class VIII SMP in science learning can be significantly feasible to use in the learning process. The conclusions are obtained from the results obtained in the description of the data shown, which indicates a positive response when the trial is carried out. Furthermore, this product will be disseminated primarily to the local school environment and other schools to provide insight into this product. Microlearning is designing learning media (short videos, infographics, pictures, articles) into small segments and focusing on the expected learning objectives. Can accommodate the limitations of media and time variations in the teaching and learning process of e-learning vibration, wave, and sound material in everyday life for students of class VIII science subjects. Keywords: Microlearning, Vibration, Waves, and Sound